Nutrition Education About Complementary Foods for Breast Milk Based on Local Food for Toddlers in the Gondangrejo Area: Pendidikan Gizi Tentang Makanan Pendamping ASI Berbasis Makanan Lokal Pada Balita di Wilayah Gondangrejo - Aryanti Setyaningsih; Erlyn Hapsari (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
Toddlers aged 6 – 24 months experience an increase in energy requirements so that complementary foods are needed to provide breast milk. MPASI is provided by the mother and when making it, you need to pay attention to the type, quantity and frequency of giving according to the age of the toddler. Making MPASI at home can use a variety of local food ingredients so that it can meet the nutritional needs of toddlers. One effort to increase mothers' knowledge and skills in making MPASI is by providing nutrition education. Nutrition education was carried out for mothers of toddlers in March - August 2021. In nutrition education, participants were given knowledge about MPASI and examples of MPASI menus using local ingredients, for example Moringa leaves. Moringa leaves contain high levels of protein and iron so they are suitable for making MPASI. Activity evaluation was carried out to determine the increase in knowledge after being given nutrition education regarding MPASI. Based on the results, it is known that 79% of mothers of toddlers have good knowledge after being given nutrition education regarding MPASI. It is hoped that in the future not only knowledge will increase but there will be maternal compliance and the implementation of giving MPASI to toddlers to support optimal growth and development of toddlers.